Al-Kafaâ€™ah al-Taâ€˜lÄ«miyyah Laday Muâ€˜allimiy al-Lughah al-â€˜Arabiyyah wa AtharuhÄ â€˜ala NatÄâ€™ij Taâ€˜allum al-TÌ£alabah al-JÄmiâ€˜ah - Rokhman, Imam Athoir (Universitas Islam Negeri Walisongo Semarang - Indonesia, 2020)
This study aims to discuss the correlation between pedagogic competence of lecturer of Arabic language especially lecturer who tries competence of language material with student learning result in Arabic language departement, Faculty of Education and Teacher Training, State Islamic University Maulana Malik Ibrahim Malang. In this study researchers used a quantitative approach and this type of research is descriptive and correlation. Instruments used in data collection are interviews, observations, questionnaires and documents. The result of the research is pedagogic competence of lecturer of language competence which includes on the ability of learning method development, implementation in learning process and implementation of evaluation is in good and based on the data analysis that has been done by the researcher showed that the condition of pedagogic competence of lecturer of language competence influence the student learning result, it is based on result of t test which amounted to 9,548 with result of sig 0,000 and t value (9,548) t table (); it can be concluded that ho is rejected and ha is accepted.